Nonstoichiometric In–S group yielding efficient carrier transfer pathway in In2S3 photoanode for solar water oxidation - Runyu Chen; Linxing Meng; Changda Wang; Weiwei Xu; Yulong Huang; Li Song; Liang Li (SusMat, 2024)
Abstract The construction of high‐efficiency photoanodes is essential for developing outstanding photoelectrochemical (PEC) water splitting cells. Furthermore, insufficient carrier transport capabilities and sluggish surface water oxidation kinetics limit its application. Using a solvothermal annealing strategy, we prepared a nonstoichiometric In–S (NS) group on the surface of an In2S3 photoanode in situ and unexpectedly formed a type II transfer path of carrier, thereby reducing the interfacial recombination and promoting the bulk separation. First‐principles calculations and comprehensive characterizations demonstrated NS group as an excellent oxygen evolution cocatalyst (OEC) that effectively facilitated carrier transport, lowered the surface overpotential, increased the surface active site, and accelerated the surface oxygen evolution reaction kinetics by precisely altering the rate‐determining steps of * to *OH and *O to *OOH. These synergistic effects remarkably enhanced the PEC performance, with a high photocurrent density of 5.02 mA cm−2 at 1.23 V versus reversible hydrogen electrode and a negative shift in the onset potential by 310 mV. This work provides a new strategy for the in situ preparation of high‐efficiency OECs and provides ideas for constructing excellent carrier transfer and transport channels.